2015
DOI: 10.1111/ajt.13252
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of BKV-specific Immunity From Pretransplantation to Posttransplantation Identifies Kidney Transplant Recipients at Increased Risk of BKV Replication

Abstract: Quantification of BKV-load and BKV-specific immunity have been evaluated to monitor BKV-replication and outcomes in kidney transplant recipients (KTRs) with BKV-infection. However, it remains crucial to better understand how immune markers can predict the risk for later infection. We studied all KTRs between 2008 and 2011. Twenty-four KTRs were diagnosed with BKVreplication and a control group of 127 KTRs was used for comparison. Samples were collected before at þ1, þ2, and þ3 months posttransplantation. BKV-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
76
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 31 publications
8
76
1
2
Order By: Relevance
“…T cell responses to the LVGR‐encoded capsid viral protein VP1 were generally more pronounced than those to EVGR‐encoded viral proteins 30, 35, 49. Interferon γ (IFN‐γ) responses were largely derived from CD4 + T cells and, to a lesser extent, from CD8 + T cells 30, 35, 51, 52, 53. Because most of these studies used overlapping 15mer peptide pools (15mP), the contribution of individual CD8 + T cell–restricted epitopes to these responses is largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…T cell responses to the LVGR‐encoded capsid viral protein VP1 were generally more pronounced than those to EVGR‐encoded viral proteins 30, 35, 49. Interferon γ (IFN‐γ) responses were largely derived from CD4 + T cells and, to a lesser extent, from CD8 + T cells 30, 35, 51, 52, 53. Because most of these studies used overlapping 15mer peptide pools (15mP), the contribution of individual CD8 + T cell–restricted epitopes to these responses is largely undefined.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed association between the recovery of BKV-specific T-cell response and viral clearance in renal transplant recipients [1,15,16,[19][20][21][22]. Therefore, in association with viral load determination, measuring BKV-specific Tcell response might be a useful tool in the management of BKV replication and assessment of response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In two previous studies, BKV-specific T-cell responses of renal transplant recipients were monitored by the ELISPOT method using five BKV antigens individually for stimulation of PBMCs [20,21]. A mixture of overlapping peptide pools including all five BKV antigens was first used for flow cytometric analysis of BKV-specific T-cells by Trydzenskaya et al and this method was suggested to be a fast approach allowing a comprehensive assessment of total BKV-specific T-cell response [24].…”
Section: Introductionmentioning
confidence: 99%
“…18 Impaired BKV-specific cell-mediated immune response is associated with BKV nephropathy, and BKV-specific immune monitoring has been suggested as a prognostic tool to identify patients who are at risk of BKV nephropathy. [19][20][21][22][23] Monitoring pretransplant and posttransplant BKV-specific T cells was suggested by Schachtner and associates 24 as a sensitive marker to identify kidney transplant recipients at increased risk of BKV reactivation. They studied 24 recipients with BKV replication and compared these patients with a control group of 127 recipients without BKV replication.…”
Section: Introductionmentioning
confidence: 99%
“…Recipients with BKV reactivation showed significantly lower CD3-positive, CD4-positive, and CD8-positive T cells and interferon gamma levels posttransplant, but with significantly higher alloreactive T cell levels (P < .05), thereby making a case for immunosurveillance as a predictor of disease progression and resolution. 24 However, this has not been studied in the context of an anti-BKV treatment strategy.…”
Section: Introductionmentioning
confidence: 99%